Inter-arm coordination and intra-cyclic variation of the hip velocity during front crawl resisted swimming - Gourgoulis, V.; Aggeloussis, N.; Boli, A.; Michalopoulou, M.; Toubekis, A.; Kasimatis, P.; Vezos, N.; Mavridis, G.; Antoniou, P.; Mavrommatis, G. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of the study was to assess the acute effect of front crawl sprint resisted swimming on the inter-arm coordination and the fluctuation of the swimming velocity. Methods: Nine female swimmers swam four all-out trials of 25 m, without and with low, moderate and high added resistance. Four camcorders were used to record the underwater movement. The inter-arm coordination was quantified using the index of coordination and the hip intra-cyclic velocity variation was analysed by calculating the coefficient of variation and the difference between the maximum and minimum velocities normalized for the mean stroke cycle velocity. Results: One-way repeated measures analyses of variance showed that swimmers change their inter-arm coordination from a "catch up" toward an "opposition" mode. Concerning the hip horizontal intra-cyclic velocity variation, it was increased significantly during resisted swimming. Conclusion: These findings indicate that although resisted swimming cause an increase in the index of coordination and consequently it could be speculated a better propulsive continuity, the velocity fluctuations of the hip within a stroke cycle are not decreased, probably due to the inability of the swimmers to overcome effectively the concrete added resistances used in this study. Thus, at least concerning its acute effect, the hypothesis that the sprint resisted swimming could led to a technical improvement can not be satisfied.